123I-Ioflupane dopamine transporter imaging (DaTSCAN) appearances in relation to emotional responsiveness, impulsivity and olfaction in suspected Parkinsonian syndrome. Issue 11 (November 2020) - La Torre, Guglielmo; Herman, Aleksandra Maria; Jessop, Maryam; Abdula, Nadia; Crawshaw, Ania; Begley, Patrick; Wroe, Emma; Saha, Romi Anirban; Duka, Theodora; Dizdarevic, Sabina
Abstract : Objective: The aim of our study was to ascertain relationships between DaTSCAN, olfactory loss, behavioural and subjective measurements of impulsivity and emotional responsiveness in patients with clinically suspected Parkinsonian syndrome (PS). Methods: A prospective study of 20 drug-naive patients with parkinsonism, underwent the University of Pennsylvania Smell Identification Test, impulsivity measurements and mood-state-questionnaires before visual and semi-quantitative DaTQUANT analyses. There were two subgroups: nine patients with scans without evidence of dopaminergic deficit (SWEDD – controls) and 11 patients with PS. Results: The PS group reported lower non-planning impulsivity than the SWEDD group ( P = 0.039). A positive correlation was found between the non-planning impulsivity ratings and right anterior putamen/background (bck) ratio in PS group ( r = 0.598, P = 0.068). Higher ratings of anger ( r = 0.575, P = 0.016), fatigue ( r = 0.746, P = 0.001), confusion ( r = 0.561, P = 0.019) and depression were positively correlated with putamen/caudate ratios (R > L) on DaTSCAN. Higher self-reported arousal was associated with lower right putamen/caudate ratio ( P = − 0.581, P = 0.014). Only fatigue was positively correlated with putamen/bck ( r = 0.564, P = 0.018). The degree of smell deficit correlated negatively with performance on reflection impulsivity tasks ( r = −0.470, P = 0.049). Conclusion: DaTSCAN appearances correlated with emotional dysfunction and self-reported impulsivity in patients with PS. Olfactory impairment was associated with increased reflection impulsivity and the age of patients. Higher DaTSCAN putamen/caudate ratios were associated with higher emotional responsiveness and higher non-planning impulsivity in PS patients. These preliminary findings may be relevant in clinical practice in differentiating PS from SWEDD and identifying susceptibility to impulse control disorder although larger studies are warranted.